1986
DOI: 10.1073/pnas.83.11.4071
|View full text |Cite
|
Sign up to set email alerts
|

Ethanol stimulates gamma-aminobutyric acid receptor-mediated chloride transport in rat brain synaptoneurosomes.

Abstract: The effects of ethanol on Cl-uptake were studied using a cell-free subcellular preparation from brain that contains a y-aminobutyric acid (GABA)/barbiturate receptor-sensitive Cl transport system. In isolated vesicles prepared from rat cerebral cortex, ethanol, at concentrations that are present during acute intoxication (20-50 mM), stimulated 36CI-uptake in a concentration-dependent and biphasic manner. The ethanol-stimulated uptake of 36CI-was markedly inhibited by the GABA antagonists picrotoxin and bicucul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
179
0
4

Year Published

1989
1989
2008
2008

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 429 publications
(188 citation statements)
references
References 27 publications
5
179
0
4
Order By: Relevance
“…For example, it was observed that ethanol enhanced GABAinduced chloride flux in synapto-neurosomes (Suzdak et al, 1986b). Other studies of cultured neurons seemed consistent with ethanol having an action on GABA A receptors at concentrations below 100 mM (Aguayo, 1990;Reynolds and Prasad, 1991;Reynolds et al, 1992; see review by Mihic, 1999).…”
Section: In Vitro Examination Of Ethanol Action On Gaba a Receptor Fumentioning
confidence: 85%
“…For example, it was observed that ethanol enhanced GABAinduced chloride flux in synapto-neurosomes (Suzdak et al, 1986b). Other studies of cultured neurons seemed consistent with ethanol having an action on GABA A receptors at concentrations below 100 mM (Aguayo, 1990;Reynolds and Prasad, 1991;Reynolds et al, 1992; see review by Mihic, 1999).…”
Section: In Vitro Examination Of Ethanol Action On Gaba a Receptor Fumentioning
confidence: 85%
“…Suzdak et al [6] showed that 220 mM of EtOH stimulate Cl-uptake via GABA receptor-coupled chloride ion channels in cerebral cortical synaptosomes, but subintoxicating concentrations (I 10 mM) potentiate both muscimol-and pentobarbital-stimulated Cl-uptake. In the present work the range of concentrations of EtOH used was 1.74-174 mM, a relatively low level when compared to the values seen in the literature [6,26]. The effects seen on the NMDA-activated channel currents at such a low concentration may not be due to unspecific effects of EtOH on the membrane lipids themselves.…”
Section: Discussionmentioning
confidence: 99%
“…Behavioral and neurochemical evidence suggests that alcohol exerts pharmacological effects remarkably similar to GABA A receptor modulators, including 3␣,5␣-THP (Suzdak et al, 1986b;Grobin et al, 1998). Several ethanol effects are enhanced by the positive GABA A receptor modulators benzodiazepines and barbiturates, but are blocked by GABA A receptor antagonists and inverse agonists (Suzdak et al, 1986a;Nutt and Lister, 1989;Givens and Breese, 1990;Liu and Deitrich, 1998).…”
Section: Abstract: Neuroactive Steroids; Ethanol; Allopregnanolone; mentioning
confidence: 99%